Film Dokumenter Budaya Betawi Ondel-Ondel di Negeri Silancang Kuning Berdasarkan Sinematografi Teknik Pengambilan Gambar - Arta Uly Siahaan; Muhammad Daru Kardewa (JURNAL INTEGRASI, 2017)
The Betawi culture is increasingly marginalized because Jakarta is experiencing rapid urbanization, excessive so that the onset of competition in the world of work and many people Were going to leave his hometown to which many have worked such as Batam city. Batam city is one of the cities with high economic growth rates so that Betawi people come to Batam for getting job. Based on an initial survey, it shows that Betawi culture is not really famous among the citizens in Batam. This research aims to make a documentary film to provide information that is more apparent in dissemination to the public of the Betawi and Batam City Community. The film is a cinematographic technique which provides information used in the filming of documentaries. The film is packed into a CD that will be submitted to the Chairman of the Betawi forum in Batam and society Betawi of Batam City Community. Based on the try out, this film is well received and successfully gives information about the culture of the Betawi non Betawi and Betawi that exist in Batam city.